Effect of Lotus Petal (Nymphaea lotus) and Pollen (Nelumbo nucifera) on Chemical and Physical Properties of Gummy Jelly Lotus Flavor - Chuchird, Pornpachen; Pattarathitiwat, Paponpat (Food Agricultural Sciences and Technology, 2021)
The research was aimed to determine the appropriate amount of lotus petals and lotus pollen on the physical and chemical properties of gummy jelly lotus flavor. The research was found that the appropriate amounts of lotus petal adding into jelly product was 25%. The sensory scores including color, flavor, sweet, texture and overall acceptance were 4.20 3.20 3.60 4.05 and 4.15, respectively. The colors value (L*, a*, and b*) were 26.12 3.72 and 7.62, respectively. The moisture content and water activity equal to 36.87 and 0.93, respectively. The hardness value of gummy jelly was 2.56 kgf. For the part of effects of lotus pollen on the quality of jelly, It was found that the appropriate amount of lotus pollen was 3% of dry ingredients. The amount of lotus pollen did not affect the texture of gummy jelly. The color values (L*, a*, and b*) were 27.44 4.00 and 5.70, respectively. The moisture content and water activity were 55.29 and 0.89, respectively. The total phenolic content in the final product was 59.74 (mg GAE/g). Moreovcer, a sample of gummy jelly was composed of camphor menthol and γ-terpinene flavor which was expressed the good characteristic of jelly product